Wireless sensor security issues on data link layer: a survey - Zulkifl Hasan, Muhammad; Mohd Hanapi, Zurina; Zunnurain Hussain, Muhammad (Tech Science Press, 2023)
via a communication medium like the internet. Computer network development has proposed how humans and devices communicate today. These networks have improved, facilitated, and made conventional forms of communication easier. However, it has also led to uptick in-network threats and assaults. In 2022, the global market for information technology is expected to reach 170.4 billion. However, in contrast, 95 of cyber security threats globally are caused by human action. These networks may be utilized in several control systems, such as home-automation, chemical and physical assault detection, intrusion detection, and environmental monitoring. The proposed literature review presents a wide range of information on Wireless Social Networks (WSNs) and Internet of Things (IoT) frameworks. The aim is first to be aware of the existing issues (issues with traditional methods) and network attacks on WSN and IoT systems and how to defend them. The second is to review the novel work in the domain and find its limitations. The goal is to identify the areas primary gray field or current research divide to enable others to address the range. Finally, we concluded that configuration. Message Rapid Spanning Tree Protocol (RSTP) messages have higher efficiency in network performance degradation than alternative Bridge Data Unit Protocol (BPDU) forms. The research divides our future research into solutions and newly developed techniques that can assist in completing the lacking component. In this research, we have selected articles from 2015 to 2021 to provide users with a comprehensive literature overview.